High-flow bypass with radial artery graft for cavernous carotid aneurysm - Kumar, Ambuj; Sharma, Raghavendra; Tanaka, Riki; Yamada, Yashuhiro; Takizawa, Katsumi; Kato, Yoko (Asian Journal of Neurosurgery, 2020)
Cavernous carotid aneurysms can be managed by different surgical as well as endovascular methods. The aim of treatment is to exclude the aneurysm from circulation and maintain normal cerebral blood flow. We are reporting a case of incidentally detected CCA managed by high flow bypass with radial artery graft. We discuss the surgical technique and nuances of high flow bypass surgery.
Keywords: Cavernous carotid aneurysm; high-flow bypass; radial artery graft